Engaging society and building participatory governance in a rural landscape restoration context. (March 2022) - Palmer, Carolyn G.; Fry, Anthony; Libala, Notiswa; Ralekhetla, Mateboho; Mtati, Nosiseko; Weaver, Matthew; Mtintsilana, Zintle; Scherman, Patricia-Ann
Abstract: Although the Anthropocene has heralded unprecedented recognition of, and concern about the consequences of landscape degradation to humans, pathways to effective long-term landscape restoration remain uncertain. Restoration is a human activity that resists negative trajectories of environmental change, whereas participatory governance involves relationality between those entrusted with formal governance of natural resources and those who directly use, benefit from, and impact on natural resources. This paper outlines the transdisciplinary approach of the Tsitsa Project in the Eastern Cape Province of South Africa to restore a degraded rural landscape. The project aspires "To support sustainable livelihoods for local people through integrated landscape management that strives for resilient social-ecological systems, and which fosters equity in access to ecosystem services". In the project, landscape management has included extensive restoration aimed to reduce erosion, increase grazing vegetation-cover, and reduce river silt loads. It has also involved engagement in a reflexive learning process with local residents, government officials and traditional leaders to derive a Capability Pathway for the development of participatory governance. A foundational step, Co-Knowing, initiates the pathway. The concept of epistemic justice guided the goal of fair inclusion among participants, the development of a shared vocabulary and the conceptual understanding required for local people to move towards real governance participation. Narratives from stakeholders provide evidence that the process is building participatory governance agency. These approaches provide credible evidence for the value of building participatory governance capabilities as a foundation for long-term restoration outcomes. Graphical Abstract: ga1